Uma proposta de ensino de logaritmos por meio da História da Matemática - Pinto, Bruno Gustavo Soares (2022)
In this work, motivated by the difficulty of the first author to learn about logarithms in high school and thus seeking to improve the mathematics learning of high school students in logarithms, we carried out a historical study on this subject, understanding the role and evolution of logarithms in the development of mathematics. In addition, we searched the existing literature, specifically in some databases, for research papers that deal with the teaching of logarithms. From the results of this research on teaching mathematics from a historical context, we developed a table with the main texts, so that, in this way, we could analyze the way of working used in the teaching and learning of logarithms. At the end of the work, we propose, based on the Problematizing Basic Units (UBPs), a proposal of activities for teaching logarithms through the History of Mathematics where we present the fundamental principles of the creation of logarithms, rescuing the role of Arithmetic and Geometric Progressions in this process.